Tutor Support of the Educational Process of Junior Schoolchildren with ASD: «Class Tutor» Intervention - E.V. Rudneva; E.Y. Davydova; S.A. Tyushkevich; E.F. Shvedovskiy; A.V. Khaustov (Moscow State University of Psychology and Education, 2022)
The heterogeneity and complexity of autism spectrum disorders (ASD) determines the need to develop special education and support environment for children with ASD, considering children special educational needs. Tutor support is a necessary, guaranteed and learning model-independent condition for the effective adaptation of a child with autism in the school environment. The «Class tutor» technology is an original education intervention developed within the framework of the concept of inclusive education. The technology focuses on the group tutor support in a grade for children with ASD. Goals of the intervention are: the adaptation of students to the educational process the individual inclusion of the student in the team; participation of a tutor in group lesson activities and tutor assistance to the group in the mastering of the education program (special type of the educational program for children with ASD); developing of the individual learning conditions, developing of the functional skills and reducing of the episodes of unwanted behavior. The specific tasks of the stages (preliminary, adaptive-diagnostic, main, final) of the technology implementation are presented. During the work with the unwanted behavior tutor uses following applied behavioral analysis techniques implemented in the «Class tutor» intervention: the use of motivational stimuli; the dosed use of prompts of various levels; extinction; positive weakening; the establishment of instructional control; an increase in the period of problem-free behavior; support and consolidation of alternative and replacing forms of behavior, maintaining an adequate pace of work; training functional communication. The game interaction during the break has been chosen as the model for the description of the intervention scheme. The principles of the intervention effectiveness study design include multiple case and multiple-baseline methodology.